The Effect of Removing Sentencing Credits on Inmate Misbehavior - Steiner, Benjamin (Journal of quantitative criminology, 2019)
To examine the effect of prison officials' decisions to remove good time credits in response to prison rule violations on subsequent inmate misbehavior.